THE INFLUENCE OF LEADERSHIP STYLE, TEAM COOPERATION, COMMUNICATION, AND COMPENSATION TOWARDS WORKING MOTIVATION OF THE HARBOURMASTER EMPLOYEES IN TANJUNG PERAK HEAD OFFICE - Setiyanto, Ari; Pamuji, Eko (Economic and Bussiness Faculty, Dr Soetomo University, 2020)
This study aims to determine and analyze the influence of leadership style, teamwork, communication, and compensation to employee work motivation. The sampling technique uses purposive sampling. Based on calculations using the Slovin formula, samples were 142 respondents. Data analysis techniques used multiple linear regression, F test, and t test. Based on the results of the study note that the leadership style, teamwork, communication, and compensation simultaneously affect work motivation as evidenced by the results of the F test which shows the significance value is smaller than 0,05 which is equal to 0,000. Leadership style, teamwork, communication, and compensation partially affect work motivation as evidenced by the results of the t test that shows the significance value of leadership style, teamwork, communication, and compensation smaller than 0,05, namely leadership style by 0,005, teamwork by 0,000, communication by 0,002, and compensation by 0,007. Teamwork has a dominant effect on work motivation as evidenced by the results of the t test which shows the significance value of teamwork is smaller than the value of the other independent variables which is equal to 0,000.